2008
DOI: 10.1002/clc.20324
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Aldosterone‐blocking Agents Eplerenone and Spironolactone

Abstract: Improved understanding of the adverse pharmacological properties of aldosterone has prompted investigation of the clinical benefits of blocking aldosterone at the receptor level. This article reviews the pharmacology, clinical efficacy, and tolerability of the two available blocking agents, spironolactone and eplerenone. A Medline search identified clinical studies assessing spironolactone and eplerenone. Priority was given to large, wellcontrolled, clinical trials and comparative studies. Pharmacological diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
155
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(164 citation statements)
references
References 33 publications
(47 reference statements)
1
155
0
8
Order By: Relevance
“…When we combine these observations with the data from overseas and look at the influence of eplerenone on serum potassium levels at this dose, no dose-dependent changes in potassium levels are ever seen within this range. 21 White et al 17 conducted a placebocontrolled study to determine the antihypertensive effects of eplerenone at 25, 50, 100 and 200 mg per day in 310 patients with essential hypertension. After 12 weeks of treatment, one patient each from the placebo and eplerenone 200 mg groups developed hyperkalemia of X5.5 mEq l À1 , but the authors concluded that the increased dose of eplerenone was not associated with the serum potassium increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When we combine these observations with the data from overseas and look at the influence of eplerenone on serum potassium levels at this dose, no dose-dependent changes in potassium levels are ever seen within this range. 21 White et al 17 conducted a placebocontrolled study to determine the antihypertensive effects of eplerenone at 25, 50, 100 and 200 mg per day in 310 patients with essential hypertension. After 12 weeks of treatment, one patient each from the placebo and eplerenone 200 mg groups developed hyperkalemia of X5.5 mEq l À1 , but the authors concluded that the increased dose of eplerenone was not associated with the serum potassium increase.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, eplerenone is indicated for heart failure in 460 countries based on its anticipated beneficial cardiac effect. 7 It has been reported that eplerenone also has a stable antihypertensive effect, [13][14][15][16][17][18][19][20] with a profile slightly different from that of spironolactone, 21 and fewer adverse reactions, suggesting that it may become a first-line treatment for hypertension. However, clinical data on hypertensive patients in Japan are lacking for eplerenone.…”
Section: Introductionmentioning
confidence: 99%
“…в 2005 г. описали подобное неренальное негеномное влияние альдостерона на миокард человека [16]. Так-же существуют и другие работы, свидетельствующие о том, что альдостерон ухудшает сократимость и мета-болические функции ишемированного миокарда, по-вышает системное сосудистое сопротивление, а также усиливает вазоконстрикторный эффект ангиотензина II в коронарных артериях [17][18][19].…”
Section: роль альдостерона в патологических процессах сердечно-сосудиunclassified
“…Unlike spironolactone, it has fewer androgenic effects (gynecomastia, mastalgia, feminization, impotence) 3. Its main side effects include hyperkalemia 3, hypotension, and renal impairment.…”
mentioning
confidence: 99%